Improve the nutritional value and utilization of rice straw via an ensiling process with different sources of energy and nitrogen enrichment - Fawzy Mohamed Abo-Donia; Mohamed Ahmed El-Shora; Wasef Abd-Elaziz Riad; Nabeel Basuony Elgamal; Wael Abdel-Menaem El-Hamady (Journal of Applied Animal Research, 2022)
Ensiled rice straw using, water (RSW), molasses plus urea, and whey (RWh) were implied to investigate the ensiling processing on palatability and nutritional value of rice straw compared to untreated rice straw (URS). Using whey resulted in a significant (P < .05) progress in fermentation coefficient, and Flieg Score compared to others. Protein and water-soluble carbohydrates content increased (P < .05) in RWh compared to RMU. Gas cumulative increased (P < .05) with ERS compared to the incubation of URS. In-vitro organic matter degradability, neutral detergent fiber degradability, crude protein degradability, microbial protein, and metabolizable energy varied less amongst the tested ingredients. The RWh was significantly (P < .05) consumed and palatable higher compared to RMU, which was more (P < .05) significant than RSW. The use of either RWh or RMU has improved total digestible nutrients (TDN) compared to RSW and URS. The values of total protein, alanine aminotransferase, and glucose were higher (P < .05) with ERS feeding compared to URS. The results indicate the possibility of ensiling rice straw with added either whey or molasses with urea as sources of nitrogen and energy to induce good fermentation and improve utilization of rice straw.